INNOVATIVE-THEMATIC BASED INTEGRATED SCIENCE LEARNING ON NATURAL DIVERSITY THEME TO IMPROVE STUDENTS’ CRITICAL THINKING SKILLS IN JUNIOR HIGH SCHOOL - Pursitasari, Indarini Dwi; Nuryanti, Siti; Rede, Amran (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
Critical thinking skills should be trained and practiced in the learning process. This study aimed to describe the use of Innovative-Thematic Based Integrated Science (ITBIS) Learning Program to improve critical thinking skills of junior high school students in Palu. The study conducted in the 7th grade from one of Palu public schools and one of Palu private schools. Data were collected by observation sheet of learning performance and students activity, also test instrument for measuring students’ critical thinking skills. The data of learning performance and students activity were analyzed quantitatively, whereas the data of critical thinking skills were analyzed using descriptive and inferential statistics. The result showed that lTBIS learning can be done well either in public school and private school with average 98,03% and 90,20% respectively. ITBIS learning also improve students activity in the learning process. The average of critical thinking skills improvement (N-gain) was 68% (public school) and 63% (private school), and there were no significant differences between both of them. It showed that lTBIS learning can be used to build critical thinking skills of junior high school students.